2018
DOI: 10.21640/ns.v10i21.1538
|View full text |Cite
|
Sign up to set email alerts
|

Detection of polysaccharides in Ganoderma lucidum extracts

Abstract: Introduction: Ganoderma lucidum is one of the most worldwide known medicinal mushrooms. However, this species of mexican mushroom has notable differences compared to its similar one since it has not been studied enough so it is important to determine its characteristics once it has been cultivated and its extracts have obtained in a standardized form.Method: The polysaccharides of the extracts of Ganoderma lucidum strain CP-145 were measured by the quantum magnetic resonance analyzer MARSIII of Bruce C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, we detected more robust similarities between Gl -2 and simvastatin gene-expression activity. Our recent study demonstrated that the addition of ASA in the Gl cultivation substrate stimulates the production of more or new bioactive compounds, mainly the polysaccharides, B-methyl glucopyranoside, DL-arabinitol and ribitol, in comparison with the conventional extract (no ASA) [ 63 ]. This pattern might be the result of biotransformation processes that occur when fungal enzymes catalyze chemical modifications of a compound [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we detected more robust similarities between Gl -2 and simvastatin gene-expression activity. Our recent study demonstrated that the addition of ASA in the Gl cultivation substrate stimulates the production of more or new bioactive compounds, mainly the polysaccharides, B-methyl glucopyranoside, DL-arabinitol and ribitol, in comparison with the conventional extract (no ASA) [ 63 ]. This pattern might be the result of biotransformation processes that occur when fungal enzymes catalyze chemical modifications of a compound [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was motivated by the fact that Xanthenedione molecules are crucial heterocyclic compounds that were extensively used for their antibacterial activity, antifungal, anti‐inflammatory drug and antiviral activity . Because of the variety of their applications, the synthesis of xanthenedione compounds has received a special attention and consideration . Specifically, Vitamin‐K nucleus [28.29] shows a variety of biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, the xanthene scaffolds 17 are one of the important heterocyclic compounds 18 and are extensively used as dyes, uorescent ingredients for visual imaging of the bio-molecules, and in optical device technology because of their valuable chemical properties. 19 The xanthene molecules have conjointly been expressed for their antibacterial activity, 20 photodynamic medical care, anti-inammatory drug impact, and antiviral activity. Because of their various applications, the synthesis of these compounds has received a great deal of attention.…”
mentioning
confidence: 99%